Chlamydia pneumoniae - prevalenca protiteles pri zdravi populaciji in bolnikih z doma pridobljeno pljučnico - Keše, Darja (Zdravniški vestnik, 2001)
Background. To determinate the prevalence rates of Chlamydia pneumoniae infections in Slovenia and to evaluate the importance of C. pneumoniae infections at patients with community acquired pneumonia (CAP). Materials and methods. With the microimmunofluorescence test (micro-IF) we evaluated the presence of C pneumoniae specific antibodies in 1036 healthy subjects, in two periods of time, in 1991-93 and 1997-1998. We also tested the pair sera collected from 2118 patients with CAP between 1993-1999. Results. We demonstrated that C. pneumoniae infections are common in our population, as wedetected IgG antibodies in 43.1% of healthy population. The prevalence rate of C. pneumaniae infectians statistically significant increased in two periodsof time. Acute C. pneumoniae infections were proved in 15.9% of all patients with CAP. Conclusions. C. pneumoniae is important respiratory pathogen also in aur community. The infections are more common in older patients. Because C. pneumoniae like other Chlamydia species has tendency to cause chronic disease, it is reasonable to diagnose this bacterium in respiratory patients. It is also recommended to test canvalescent sera at serologic laboratory diagnosis.
Keywords: Antibodies, bacterial; bacteria; bakterije; bakterijske infekcije; Chlamydia infections; Chlamydia pneumoniae; Community-acquired infections; Diagnosis; epidemiologija; Epidemiology; IgG; Immunology